The Influence of the use of Kahoot Game-Based Learning Media on Students' Learning Motivation in the Subject of Food Presentation at Vocational School - Melani Andina; Elida Elida; Wiwik Indrayeni; Cici Andriani (Educia Journal, 2026)
The integration of digital technologies into vocational education has created opportunities to improve students' learning motivation through more interactive and student-centered instructional approaches. This study aims to examine the effect of Kahoot game-based learning media on students' learning motivation in the Food and Beverage Service subject at SMK Negeri 6 Padang, Indonesia. A quantitative approach employing a true experimental design with a Posttest-Only Control Group Design was adopted. The study involved 72 Grade XI Culinary students selected through simple random sampling and assigned equally to an experimental group receiving Kahoot-assisted instruction and a control group receiving conventional PowerPoint-based instruction. Data on students' learning motivation were collected using a validated four-point Likert-scale questionnaire based on six motivational indicators proposed by Uno. Descriptive statistics and inferential analyses were conducted using IBM SPSS Statistics Version 20. Prior to hypothesis testing, data normality and homogeneity assumptions were verified using the One-Sample Kolmogorov–Smirnov test and Levene's Test, respectively. The results revealed that the experimental group achieved a higher mean motivation score (135.61) than the control group (112.94). The Independent Samples t-test indicated a statistically significant difference between the two groups (t = 10.921, p < 0.001), confirming that Kahoot game-based learning media significantly improved students' learning motivation. These findings suggest that game-based learning functions not only as an instructional technology but also as an effective instructional management strategy that promotes active participation, immediate feedback, and sustained classroom engagement. The study contributes to the educational management literature by providing empirical evidence supporting the integration of gamified digital learning into vocational education and offers practical implications for teachers and school leaders seeking to strengthen instructional quality through technology-enhanced learning.